Myasthenia Gravis-Like Syndrome Presenting as a Component of the Paraneoplastic Syndrome of Lung Adenocarcinoma in a Nonsmoker - Sahar Eivaz-Mohammadi; Fernando Gonzalez-Ibarra; Hesam Hekmatjou; Rao Mikkilineni; Amit Patel; Amer K. Syed (Case Reports in Oncological Medicine)
Adenocarcinoma of the lung is the most common form of lung cancer in nonsmokers. It is commonly seen in the periphery of the lungs. Myasthenia gravis is generally associated with mediastinal malignancies and rarely associated with adenocarcinoma of the lung. We present a case of a 38-year-old male nonsmoker with rapidly progressive adenocarcinoma of the lung associated with myasthenia gravis, a patient whom expired within 27 days of hospital admission and diagnosis.